Responses to trade opening: Evidence and lessons from Asia - Devashish Mitra (Asian Development Bank Institute (ADBI), 2019)
In various Asian countries, international trade has raised productivity, lowered markups through import competition (while increasing them through cheaper inputs that can be imported), raised wages, expanded employment, and, above all, reduced poverty. This is in sharp contrast to the impact of trade in some of the Latin American countries, which suggests exercising caution in extrapolating results to Asian countries that have not yet been studied. There are also a few adverse consequences of trade that already been found for Asia. Apart from raising inequality, trade can increase informality, especially in the presence of labor-market rigidities. Additionally, there are the adverse effects stemming from trade adjustment as a result of worker mobility costs. In this context, this study discuss various policies that researchers have recommended.
Keywords: F10; F13; 330